In situ combinatorial synthesis of degradable branched lipidoids for systemic delivery of mRNA therapeutics and gene editors - Xuexiang Han; Junchao Xu; Ying Xu; Mohamad-Gabriel Alameh; Lulu Xue; Ningqiang Gong; Rakan El-Mayta; Rohan Palanki; Claude C. Warzecha; Gan Zhao; Andrew E. Vaughan; James M. Wilson; et al. (Nature Communications, 2024)
Abstract The ionizable lipidoid is a key component of lipid nanoparticles (LNPs). Degradable lipidoids containing extended alkyl branches have received tremendous attention, yet their optimization and investigation are underappreciated. Here, we devise an in situ construction method for the combinatorial synthesis of degradable branched (DB) lipidoids. We find that appending branch tails to inefficacious lipidoids via degradable linkers boosts mRNA delivery efficiency up to three orders of magnitude. Combinatorial screening and systematic investigation of two libraries of DB-lipidoids reveal important structural criteria that govern their in vivo potency. The lead DB-LNP demonstrates robust delivery of mRNA therapeutics and gene editors into the liver. In a diet-induced obese mouse model, we show that repeated administration of DB-LNP encapsulating mRNA encoding human fibroblast growth factor 21 alleviates obesity and fatty liver. Together, we offer a construction strategy for high-throughput and cost-efficient synthesis of DB-lipidoids. This study provides insights into branched lipidoids for efficient mRNA delivery.